2019
DOI: 10.1186/s13550-019-0583-9
|View full text |Cite
|
Sign up to set email alerts
|

The role of 18F-FCH PET/CT in patients with uremic hyperparathyroidism compared with 99mTc-sestaMIBI SPECT/CT and ultrasonography

Abstract: Background: The aim of this study was to evaluate the diagnostic efficacy of 18 F-fluorocholine ( 18 F-FCH) PET/CT for uremic hyperparathyroidism (uHPT) compared to 99m Tc-sestaMIBI SPECT/CT and ultrasonography (US). Methods: A total of 17 uHPT patients with stage 5 chronic kidney disease (CKD) were prospectively enrolled. All patients underwent US, 99m Tc-sestaMIBI SPECT/CT, and 18 F-FCH within 2 months and received surgical treatment. Visual and quantitative methods were used for image analyses. Intraoperati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…On the other hand, when we compared 18F-FCH PET/CT with the other diagnostic techniques, in particular neck US, 18F-FCH PET/CT had low specificity with higher rates of false positive results in patients with both sHPT and tHPT. These findings are consistent with the data previously reported by Xue et al [ 27 ] and Chen et al [ 28 ] in similar populations of CKD patients with HPT. A recent study revealed excellent results for PET/CT with 11C-Metionine (11C-MET) as a second-line preoperative technique after negative first-line ultrasound and scintigraphy in patients with tertiary hyperparathyroidism.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…On the other hand, when we compared 18F-FCH PET/CT with the other diagnostic techniques, in particular neck US, 18F-FCH PET/CT had low specificity with higher rates of false positive results in patients with both sHPT and tHPT. These findings are consistent with the data previously reported by Xue et al [ 27 ] and Chen et al [ 28 ] in similar populations of CKD patients with HPT. A recent study revealed excellent results for PET/CT with 11C-Metionine (11C-MET) as a second-line preoperative technique after negative first-line ultrasound and scintigraphy in patients with tertiary hyperparathyroidism.…”
Section: Discussionsupporting
confidence: 94%
“…In recent years, positron emission tomography/computed tomography (PET/CT) with 18F-fluorocholine (18F-FCH) has emerged as a second-line imaging procedure which offers high resolution, low radiation exposure in comparison with 4D CT, and shorter examination times in patients with primary HPT (pHPT), and even in patients with a history of PTX [ 22 , 23 , 24 , 25 , 26 ]. Unlike what has previously been published for pHPT, informative data on the use of 18F-FCH PET/CT in patients with CKD and HPT are limited [ 27 , 28 ]. Moreover, patients are usually analyzed without clear separation between sHPT and tHPT, which seems to be a questionable methodological choice when considering the underlying different pathophysiology.…”
Section: Introductionmentioning
confidence: 99%
“…To understand the diagnostic e cacy of 18 F-FCH PET/CT for hyperplasia and adenoma, respectively, we analyzed each lesion separately and found that the detection rate of PET/CT was signi cantly higher for adenoma than for hyperplasia (97.06% vs. 68.29%). Further analysis revealed that lesion size affected the PET imaging results of the hyperplastic lesions, with the lesions in the PET-positive group being signi cantly larger than those in the PET-negative group (1.34 ± 0.431 cm vs. 0.91 ± 0.480 cm).This may be due to the fact that smaller lesions have relatively few functional-like cells, which do not have high uptake of the imaging agent and are thus easily missed [13,14]. In addition, Boccalatte et al [15].…”
Section: Discussionmentioning
confidence: 98%
“…Few reports in the literature indicate the high usefulness of [ 18 F]FCH in preoperative diagnostics in patients with tHPT. In a Chinese study from 2019, which included a group of 17 dialysis patients with hyperparathyroidism, Xue et al assessed the sensitivity of PET/CT with [ 18 F]FCH to be 84.1% (with 100% specificity and 86.5% accuracy) [ 26 ]. Positive PET/CT results with [ 18 F]FCH were obtained in all patients included in the study, and no false positives were found.…”
Section: Discussionmentioning
confidence: 99%